Potential of Coconut Dregs Flour and Tofu Dregs Flour As An Ingredient for Snack bar Production - Yulneriwarni, Yulneriwarni (Budapest International Research and Critics University, 2024)
Waste or by-products from the food industry, such as coconut dregs and tofu dregs, are available in abundant quantities. The use of coconut dregs and tofu dregs as animal feed is generally limited. However, in both of these dregs, necessary nutrients are still present in the body Dregs. This can also be reprocessed into flour, supporting sustainable food security. Coconut dregs flour and tofu dregs flour can be used as raw materials in making several food products with economic value, such as snack bars, so that they can support product diversification. The snacks at the snack bar are stick-shaped and have a dense texture. Snack bars can be consumed as ready-to-eat food, fulfilling the necessity of public activity. This research aims to find the optimal formulation of coconut dregs flour and tofu dregs for making snack bars. The best formulation is determined in research carried out by organoleptic testing of the snack bars produced, including color, aroma, taste, and texture, which is then continued with analysis of carbohydrate content, protein content, fat content, ash content, water content, and crude fiber content. The research results show that coconut dregs flour and tofu dregs have the potential to be basic ingredients in making snack bars. From the organoleptic test results seen, the snack bar that has been rated highest by the panelists is a product made from 30% coconut pulp flour and 70% tofu pulp flour, which has quite good nutritional content and quite high fiber content.